DIVERSITY AND CRANIAL VARIATION OF MURID RODENTS IN THE REMOTE HIMALAYAN–KARAKORAM TRANSITION ZONE (INDUS KOHISTAN, PAKISTAN) (Journal of Medical & Health Sciences Review, 2025)
Murid rodents (Order Rodentia, Family Muridae) are ecologically important members of terrestrial ecosystems. Muridae is the largest family of class Mammalia and its taxonomy is difficult and debatable. They are major reservoirs of zoonotic pathogens. Kohistan is a junction for Hindukush, Karakoram and Himalayan Mountain systems. However, the rich biodiversity of Indus Kohistan is not documented systematically due to its rugged and inaccessible terrain. The three mountainous ranges converge here hence this area represents a biogeographically unique but understudied landscape. A total of 55 specimens encompassing two subfamilies, four genera, and five species were documented, 26 external and cranial morphometric traits were assessed. Diversity analysis revealed Rattus rattus as the dominant species (52.7%), followed by Rattus turkestanicus, Mus musculus, Alticola roylei, and Apodemus rusiges respectively. Shannon and Simpson indices indicated moderate but non-uniform species diversity (H = 1.27; D = 0.35). Cranial morphometrics of R. rattus showed limited sexual dimorphism. T-test of crania reveals no significant sexual dimorphism at 95% confidence interval. Principal Component analysis suggests the division of male and female specimen around Orbital length and Breadth of Foramen magnum respectively. Hierarchal Cluster analysis grouped cranial measurements into 3 main Clusters according to correlation among the measurements. These findings provide the first systematic baseline of murid diversity in Indus Kohistan and highlight their role as ecological indicators and subjects for small mammals’ management strategies. Murids are important members of terrestrial food chains and their distribution indicates health of biotic systems. A detailed study of both indoor and outdoor rodent species is necessary. Expanding genetic and ecological assessments will be essential for understanding the evolutionary history and conservation implications of small mammals in this transition zone. Therefore, the present study gives a glimpse of Murid diversity harbored by this important and developing remote region of Pakistan.